A RETROSPECTIVE STUDY IN VISAKHAPATNAM ON DELAYED CRY AT BIRTH: AN IMPORTANT PREDICTOR OF FUTURE NEURO DEVELOPMENTAL PROBLEM-ASSOCIATED FACTORS - RAO, TATAVARTI SRINIVASA; RAO, SIDDANATHI NARASINGA; SUBBALAKSHMI, TELIDEVARA DURGA POORNA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Cerebral palsy (CP) is a group of non-progressive neurological disorders caused by an injury to the area of the brain that controls muscle movement and posture. Physical and cognitive signs and symptoms that indicate CP vary widely, depending on which parts of the brain are affected, severity of the disease, and the age of the baby or child when symptoms first appear and one such symptom is delay in crying at birth. Methods: Data collected from the mothers of 177 children of CP children with history of delayed cry at birth, admitted or attended to Rani Chandramani Devi Government Hospital, Visakhapatnam from the period of 2014–2020. Results: The data collected retrospectively from the mothers of 177 CP children with history of delayed cry at birth were analyzed. Among them, 114 were male and 63 were female. Considering the age of the mother at the time of conception in the mothers of 177 CP children with delayed cry at birth, it was found that, more number of cases were reported in the maternal age between 19 and 30 years 106 (60%). The age of the mother at the time of conception, extremes of mother age both below 18 years and above 30 years, poses risk both to the mother and the fetus. In the present study, it was found to be 40%. Mothers with anemia were reported to be high 32.2% and act as a most prevalent antenatal factor of CP cases. By performing a student “t” test between the CP cases with associated factors and CP cases without associated factors, the results were highly significant p<0.001. Conclusion: Delayed cry at birth should be taken as an early hint that the child might develop neurodevelopmental problems in the future. This should alert the parents and the family physicians and should be attended with appropriate consultation of a team of doctors to address any deviations observed at an early age for a better outcome.